Inserts and Cutting Tools

JP7635415B2Active Publication Date: 2025-02-25KYOCERA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023556263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-29
Filing Date
2022-10-06
Publication Date
2025-02-25
Estimated Expiration
2042-10-06

Smart Images

  • Figure 0007635415000001
    Figure 0007635415000001
  • Figure 0007635415000002
    Figure 0007635415000002
  • Figure 0007635415000003
    Figure 0007635415000003
Patent Text Reader

Abstract

An insert (1) according to the present disclosure comprises a base material (2) and a coating layer (3) that covers the surface of the base material (2). The base material (2) is formed of a cermet. The coating layer (3) is formed of Ti1-a-b-c-dAlaMbWcSid(CxN1-x) (wherein metal element M represents one or more elements selected from among Nb, Mo, Ta, Hf and Y, 0.40 ≤ a ≤ 0.55, 0.01 ≤ b ≤ 0.1, 0.01 ≤ c ≤ 0.1, 0.01 ≤ d ≤ 0.05 and 0 ≤ x ≤ 1). In addition, an insert (1) according to one embodiment of the present disclosure has an intermediate layer (4) which contains Ti and is arranged between a base material (2) and a coating layer (3). The average thickness of the intermediate layer (4) is 20 nm to 80 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an insert and a cutting tool. [Background technology]

[0002] Cermets containing titanium (Ti) as a main component are widely used as substrates for members that require wear resistance, sliding properties, and chipping resistance, such as cutting tools, wear-resistant members, and sliding members.

[0003] Patent Document 1 discloses a cermet cutting tool in which a soluble alloy phase made of metal binder phase components is located on the surface of a cermet base containing binder phase components mainly composed of cobalt (Co) and nickel (Ni), and a TiN layer having a diffusion-preventing effect is located on the soluble alloy phase. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 3099834 Summary of the Invention

[0005] The insert according to one embodiment of the present disclosure has a substrate and a coating layer covering the surface of the substrate. The substrate is made of cermet. The coating layer is made of Ti 1-a-b-c-d Al a M b W c S d (C x N 1-x ) (wherein metal element M is one or more selected from Nb, Mo, Ta, Hf, and Y, and 0.40≦a≦0.55, 0.01≦b≦0.1, 0.01≦c≦0.1, 0.01≦d≦0.05, and 0≦x≦1.) In the insert according to one embodiment of the present disclosure, an intermediate layer containing Ti is located between the substrate and the coating layer. The average thickness of the intermediate layer is 20 nm or more and 80 nm or less. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 is a perspective view showing an example of an insert according to an embodiment. [Diagram 2] FIG. 2 is a side cross-sectional view showing an example of an insert according to an embodiment. [Diagram 3] FIG. 3 is a schematic enlarged view of a cross section of the intermediate layer. [Figure 4] FIG. 4 is a front view showing an example of a cutting tool according to an embodiment. [Diagram 5] FIG. 5 is a graph showing the results of hardness measurements. [Figure 6] FIG. 6 is a graph showing the results of measuring the compressive residual stress of the coating films of Samples No. 1 to No. 4. [Figure 7] FIG. 7 is a graph showing the results of the adhesion measurement. [Figure 8] FIG. 8 is a table summarizing the results of the hardness measurement, the stress measurement, and the adhesion measurement. [Figure 9] FIG. 9 is a diagram showing a Ti element mapping image in the intermediate layer of sample No. 1. [Figure 10] FIG. 10 is a diagram showing an Ar element mapping image in the intermediate layer of sample No. 1. [Figure 11] FIG. 11 is a table showing the element composition ratios in atomic % at the measurement points P1 to P4 shown in FIG. [Figure 12] FIG. 12 is a graph showing the results of the wear test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, a detailed description will be given of an embodiment (hereinafter, referred to as an "embodiment") for carrying out the insert and cutting tool according to the present disclosure with reference to the drawings. Note that the insert and cutting tool according to the present disclosure are not limited to this embodiment. In addition, each embodiment can be appropriately combined as long as the processing contents are not contradictory. In addition, the same parts in each of the following embodiments are given the same reference numerals, and duplicated explanations will be omitted.

[0008] In addition, in the embodiments described below, expressions such as "constant", "orthogonal", "vertical" and "parallel" may be used, but these expressions do not necessarily mean "constant", "orthogonal", "vertical" and "parallel" strictly. In other words, each of the above expressions allows for deviations due to, for example, manufacturing accuracy or installation accuracy.

[0009] It has been known that forming a coating layer on a cermet substrate increases the residual stress of the coating layer. If the residual stress of the coating layer is high, the coating layer is likely to peel off from the substrate, making it difficult to increase the wear resistance of the insert. It is possible to reduce the residual stress of the coating layer by forming a coating layer with a low hardness. However, in this case, the wear resistance of the coating layer itself decreases, making it difficult to increase the wear resistance of the insert.

[0010] For these reasons, there is a need for an insert and a cutting tool that are excellent in wear resistance.

[0011] <insert> Fig. 1 is a perspective view showing an example of an insert according to an embodiment. Fig. 2 is a side cross-sectional view showing an example of an insert 1 according to an embodiment. As shown in Figs. 1 and 2, the insert 1 according to the embodiment has a base body 2, a coating layer 3, and an intermediate layer 4.

[0012] (Base 2) The base 2 has, for example, a hexahedral shape in which the upper and lower surfaces (surfaces intersecting with the Z-axis shown in FIG. 1) are parallelograms.

[0013] One corner portion of the base body 2 functions as a cutting edge portion. The cutting edge portion has a first surface (e.g., an upper surface) and a second surface (e.g., a side surface) connected to the first surface. In the embodiment, the first surface functions as a "scooping surface" that scoops up chips generated by cutting, and the second surface functions as a "flank surface." A cutting edge is located at least in a part of the ridge where the first surface and the second surface intersect, and the insert 1 cuts the workpiece by applying the cutting edge to the workpiece.

[0014] A through hole 21 that vertically passes through the base body 2 may be located in the center of the base body 2. In this case, a screw 75 for attaching the insert 1 to a holder 70 described later is inserted into the through hole 21 (see FIG. 4).

[0015] The substrate 2 is made of a cermet. The cermet contains a hard layer and a binder phase. The hard layer may contain Ti. For example, the hard layer may be mainly composed of at least one selected from TiCN, TiC, TiN, and TiMN (M is at least one metal element selected from metals in Groups 4, 5, and 6 of the periodic table other than Ti, Al, and Si). The binder phase is mainly composed of an iron group metal such as Ni or Co. The main component may be one that occupies 50% by mass or more of the constituent components.

[0016] (Coating layer 3) The coating layer 3 is applied to the substrate 2 for the purpose of improving the abrasion resistance, heat resistance, etc. of the substrate 2. Although Fig. 2 shows an example in which the coating layer 3 covers the entire surface of the substrate 2, the coating layer 3 does not necessarily have to cover the entire surface of the substrate 2. When the coating layer 3 is located on the first surface (here, the upper surface) of the substrate 2, the abrasion resistance and heat resistance of the first surface are high. When the coating layer 3 is located on the second surface (here, the side surface) of the substrate 2, the abrasion resistance and heat resistance of the second surface are high.

[0017] The coating layer 3 may contain, for example, cubic crystals containing one or more elements selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Si, and Al in the periodic table, and one or more elements selected from the group consisting of C, N, and O. In this case, the oxidation resistance of the coating layer 3 is improved. This further improves the wear resistance of the coating layer 3.

[0018] For example, coating layer 3 may be a TiAlSiN-based layer containing Ti, Al, Si, and N. In this way, by positioning coating layer 3 containing the metal (Ti) contained in intermediate layer 4 on intermediate layer 4, adhesion between intermediate layer 4 and coating layer 3 is increased. This makes coating layer 3 less likely to peel off from intermediate layer 4, thereby increasing the durability of coating layer 3. Note that the expression "TiAlSiN" means that Ti, Al, Si, and N are present in any ratio, and does not necessarily mean that Ti, Al, Si, and N are present in a 1:1:1:1:1 ratio.

[0019] As a specific example, the coating layer 3 is made of Ti 1-a-b-c-d Al a M b W c S d (C x N 1-x ) where M is one or more metal elements selected from the group consisting of Nb, Mo, Ta, Hf, and Y. Additionally, a to d are 0.40≦a≦0.55, 0.01≦b≦0.1, 0.01≦c≦0.1, and 0.01≦d≦0.05, respectively, and x is 0≦x≦1.

[0020] The coating layer 3 may have a hardness of 33.5 GPa or more and a compressive residual stress of 1.4 GPa or less. In this case, the adhesion between the substrate 2 and the coating layer 3 is further improved. In addition, the wear resistance of the coating layer 3 is improved, thereby extending the life of the insert 1.

[0021] The adhesive strength of the coating layer 3 to the substrate 2 (hereinafter referred to as "adhesion") may be 110 N or more in terms of peel load in a scratch test. With such a configuration, the internal stress and thermal stress that determine the adhesion between the substrate 2 and the coating layer 3 are optimized, and the coating layer 3 can be made less likely to peel off while maintaining a high hardness of the coating layer 3. As a result, the life of the insert 1 is further extended.

[0022] (Method of manufacturing the coating layer) The coating layer may be formed by, for example, a physical vapor deposition method. Examples of the physical vapor deposition method include an ion plating method and a sputtering method. As an example, when the coating layer is formed by an ion plating method, the coating layer can be formed by the following method.

[0023] As an example, a method for producing a coating layer by ion plating is shown below. First, a metal target of Ti, Al, M (wherein the metal element M is one or more selected from Nb, Mo, Ta, Hf, and Y), W, or Si, or a composite alloy target, or a sintered target is prepared.

[0024] Next, the above target, which is the metal source, is evaporated and ionized by arc discharge or glow discharge. The ionized metal is reacted with nitrogen (N2) gas, which is the nitrogen source, and is evaporated onto the surface of the substrate. The above procedure allows the formation of a coating layer.

[0025] In the above procedure, the temperature of the substrate may be set to 500° C. or more and 600° C. or less, the nitrogen gas pressure may be set to 1.0 Pa or more and 6.0 Pa or less, a DC bias voltage of −50 V or more and −200 V or less may be applied to the substrate, and the arc discharge current may be set to 100 A or more and 200 A or less.

[0026] The composition of the coating layer can be adjusted by controlling the voltage and current values ​​during arc discharge and glow discharge applied to each metal target independently for each target. The composition of the coating layer can also be adjusted by controlling the composition of the metal target, the coating time, and the atmospheric gas pressure.

[0027] (Middle tier 4) An intermediate layer 4 may be located between the substrate 2 and the coating layer 3. Specifically, the intermediate layer 4 contacts the upper surface of the substrate 2 on one side and contacts the lower surface of the coating layer 3 on the other side.

[0028] The intermediate layer 4 is mainly composed of Ti. Such intermediate layer 4 has higher adhesion to the substrate 2 than the coating layer 3. The proportion of Ti in the intermediate layer 4 can be identified by, for example, analysis using an EDS (energy dispersive X-ray spectrometer) attached to a STEM (scanning transmission electron microscope).

[0029] In this manner, the insert 1 according to the embodiment has the intermediate layer 4 between the substrate 2 and the coating layer 3, which has higher wettability with the substrate 2 than the coating layer 3, and therefore has high adhesion between the substrate 2 and the coating layer 3. In addition, since the intermediate layer 4 also has high adhesion with the coating layer 3, peeling of the coating layer 3 from the intermediate layer 4 is unlikely to occur.

[0030] The average thickness of the intermediate layer 4 may be 20 nm or more and 80 nm or less. When the thickness of the intermediate layer 4 is 20 nm or more, the adhesion effect between the coating layer 3 and the substrate 2 is more effectively exhibited, and when the thickness of the intermediate layer 4 is 80 nm or less, the generation and propagation of cracks from the intermediate layer 4 is suppressed. Therefore, by setting the average thickness of the intermediate layer 4 to be 20 nm or more and 80 nm or less, the adhesion force between the substrate 2 and the coating layer 3 can be further improved, and the wear resistance and chipping resistance of the insert 1 can be further improved.

[0031] The intermediate layer 4 according to the embodiment may contain Ar in addition to Ti. The insert 1 having the intermediate layer 4 containing Ti and Ar between the substrate 2 and the coating layer 3 has a higher adhesion between the substrate 2 and the coating layer 3.

[0032] Specifically, the intermediate layer 4 containing Ti and Ar has a higher stress relaxation effect than an intermediate layer containing only Ti (not containing Ar). The intermediate layer 4 containing Ar can relax a sudden change in stress from the substrate 2 to the coating layer 3. As a result, it is believed that the adhesion between the substrate 2 and the coating layer 3 is improved.

[0033] Fig. 3 is a schematic enlarged view of a cross section of the intermediate layer 4. As shown in Fig. 3, the intermediate layer 4 may have a plurality of Ar-enriched regions 41. The Ar-enriched regions 41 are regions in which the Ar content is higher than other regions 42 of the intermediate layer 4. The presence of the Ar-enriched regions 41 can be identified, for example, by analysis using an EDS (energy dispersive X-ray spectrometer) attached to a STEM (scanning transmission electron microscope).

[0034] The Ar enriched regions 41 may be distributed in an island-like manner in the intermediate layer 4. Here, "distributed in an island-like manner" means that the Ar enriched regions 41 are present in an isolated state without contacting each other. The shape of each Ar enriched region 41 is not particularly limited. For example, the Ar enriched region 41 may be a shape composed of curved lines such as a circle or an ellipse, a shape composed of straight lines such as a polygon, or a shape composed of curved lines and straight lines.

[0035] In this way, when the multiple Ar-enriched regions 41 are distributed in an island shape, the effect of mitigating abrupt changes in stress from the substrate 2 to the coating layer 3 is further enhanced, and the adhesion between the substrate 2 and the coating layer 3 is further improved. As a result, the wear resistance and fracture resistance of the insert 1 are improved.

[0036] The multiple Ar-enriched regions 41 may be distributed more in region 4L closer to the substrate 2 than to the center in the thickness direction of the intermediate layer 4 (here, the Z-axis direction), compared to region 4U closer to the coating layer 3 than to the center in the thickness direction of the intermediate layer 4.

[0037] In this way, when the multiple Ar-enriched regions 41 are distributed more in the region on the base 2 side than in the center in the thickness direction, abrupt changes in stress from the base 2 to the intermediate layer 4 are alleviated, and the adhesion between the base 2 and the intermediate layer 4, and therefore the adhesion between the base 2 and the coating layer 3, are further improved. As a result, the wear resistance and chipping resistance of the insert 1 are improved.

[0038] The Ar-enriched region 41 may contain 3 atomic % or more of Ar. In this case, the stress generated between the substrate 2 and the coating layer 3 is alleviated, and the hardness of the coating layer 3 is improved. As a result, the wear resistance of the coating layer 3 can be improved.

[0039] The intermediate layer 4 may contain 65 atomic % or more of Ti and 1 atomic % or more of Ar. With this configuration, the hardness of the coating layer 3 can be further increased while reducing the stress generated between the substrate 2 and the coating layer 3. This improves the wear resistance of the insert 1.

[0040] The intermediate layer 4 having the above-mentioned configuration can be obtained, for example, by the following manufacturing method.

[0041] (Method of manufacturing intermediate layer) 8×10 -3 Pa or more 1×10 -4 The substrate is heated in a reduced pressure environment of 0.1 Pa or less to a surface temperature of 500°C to 600°C. Next, argon gas is introduced as the atmospheric gas, and the pressure is maintained at 3.0 Pa. Next, the bias voltage is set to -400 V, and argon bombardment is performed for 11 minutes (argon bombardment pre-treatment). Next, the pressure is reduced to 0.1 Pa, and an arc current of 100 A to 180 A is applied to the Ti metal evaporation source for 0.5 minutes to 1.0 minutes, forming a Ti-containing layer as an intermediate layer on the surface of the substrate (Ti-containing layer film formation treatment). Thereafter, argon gas is introduced as the atmospheric gas, the pressure is maintained at 3.0 Pa to 4.0 Pa, and the bias voltage is set to -200 V, and argon bombardment is performed for 0.3 minutes to 0.8 minutes (argon bombardment post-treatment).

[0042] Subsequently, the Ti-containing layer film-forming process and the argon bombardment post-treatment are alternately repeated one or more times and 20 or fewer times. When repeated once, an intermediate layer of about 10 nm is formed, and when repeated 20 times, an intermediate layer of about 200 nm is formed.

[0043] <Processing conditions of argon bombardment pretreatment> (1) Bias voltage: -400 V (2) Pressure: 3 Pa or less (3) Processing time: 11 minutes

[0044] <Processing conditions of Ti-containing layer film-forming process> (1) Arc current: 100 A or more and 180 A or less (2) Bias voltage: -400 V (3) Pressure: 0.1 Pa (4) Processing time: 0.5 minute or more and 1 minute or less

[0045] <Processing conditions of argon bombardment post-treatment> (1) Bias voltage: -200 V (2) Pressure: 3 Pa or more and 4 Pa or less (3) Processing time: 0.3 minute or more and 0.8 minute or less

[0046] <Cutting tool> Next, the configuration of the cutting tool including the insert 1 described above will be described with reference to FIG. 4. FIG. 4 is a front view showing an example of the cutting tool according to the embodiment.

[0047] As shown in FIG. 4, the cutting tool 100 according to the embodiment includes an insert 1 and a holder 70 for fixing the insert 1.

[0048] The holder 70 is a rod-shaped member extending from the first end (the upper end in FIG. 4) toward the second end (the lower end in FIG. 4). The holder 70 is made of, for example, steel or cast iron. In particular, it is preferable to use steel with high toughness among these members.

[0049] The holder 70 has a pocket 73 at the end on the first end side. The pocket 73 is a portion where the insert 1 is attached, and has a seating surface that intersects with the rotation direction of the workpiece and a constraint side surface that is inclined relative to the seating surface. The seating surface is provided with a screw hole into which a screw 75, which will be described later, is screwed.

[0050] The insert 1 is positioned in a pocket 73 of the holder 70, and is attached to the holder 70 by a screw 75. That is, the screw 75 is inserted into the through hole 21 of the insert 1, and the tip of the screw 75 is inserted into a screw hole formed in the seating surface of the pocket 73 to screw the threaded portions together. In this way, the insert 1 is attached to the holder 70 such that the cutting edge portion protrudes outward from the holder 70.

[0051] In the embodiment, a cutting tool used in so-called turning is exemplified. Examples of turning include inner diameter machining, outer diameter machining, and grooving. The cutting tool is not limited to that used in turning. For example, the insert 1 may be used in a cutting tool used in turning. Examples of cutting tools used in turning include milling cutters such as flat milling cutters, face milling cutters, side milling cutters, and groove milling cutters, and end mills such as single-blade end mills, multiple-blade end mills, tapered blade end mills, and ball end mills. EXAMPLES

[0052] Examples of the present disclosure will be specifically described below. Note that the present disclosure is not limited to the examples shown below.

[0053] Samples No. 1 to No. 4 were prepared having an intermediate layer and a coating layer on a substrate made of a cermet having a hard phase containing Ti and a binder phase containing Co and Ni. Sample No. 1 corresponds to an example of the present disclosure and has an intermediate layer containing Ti and Ar and a TiAlN-based coating layer. Specifically, Sample No. 1 has a coating layer made of TiAlNbWSiN. The specific composition of the coating layer of Sample No. 1 is Ti. 46 Al 49Nb2W2Si1(N). The manufacturing method of the intermediate layer and the coating layer is as described above. Sample No. 2 corresponds to an embodiment of the present disclosure. Sample No. 2 has an intermediate layer containing Ti and Al, and a TiAlN-based coating layer similar to that of Sample No. 1. Sample No. 3 corresponds to a comparative example. Sample No. 3 has an intermediate layer containing Al and Cr, and a TiAlN-based coating layer similar to that of Sample No. 1. Sample No. 4 corresponds to an embodiment. Sample No. 4 has an intermediate layer containing Ti but not Ar, and a TiAlN-based coating layer similar to that of Sample No. 1. For each of Samples No. 1 to No. 3, seven types of samples were prepared with intermediate layer thicknesses of 10 nm, 20 nm, 40 nm, 80 nm, 120 nm, 160 nm, and 200 nm, respectively. For Sample No. 4, one type of sample was prepared with an intermediate layer thickness of 40 nm. The thickness of the coating layer in each of Samples No. 1 to No. 4 is 3 μm.

[0054] <Hardness measurement> For samples No. 1 to No. 4, the hardness was measured (nanoindentation test) with an indenter load of 50 mN in the measurement range from the surface of the coating layer to a depth of 10% to less than 20% of the thickness of the coating layer. The measurement was performed using a microindentation hardness tester "ENT-1100b / a" (manufactured by Elionix Co., Ltd.).

[0055] Specifically, after contacting the surface of the coating layer with an indenter, the displacement of the indenter (change in indentation depth) was measured when the load was changed in the sequence of load application, maximum load holding, and unloading to obtain a load-displacement curve. The hardness was then calculated from the obtained load-displacement curve. This series of measurements was performed 15 times for each, and the average of the hardness measurements for the 15 times was calculated.

[0056] FIG. 5 is a graph showing the results of hardness measurement. The horizontal axis of the graph shown in FIG. 5 is the intermediate layer thickness (nm), and the vertical axis is the hardness (GPa) of the coating layer. The data shown by squares in FIG. 5 shows the hardness of the coating layer of sample No. 1. The data shown by open circles in FIG. 5 shows the hardness of the coating layer of sample No. 2. The data shown by triangles in FIG. 5 shows the hardness of the coating layer of sample No. 3. The data shown by filled circles in FIG. 5 shows the hardness of the coating layer of sample No. 4. In FIG. 5, the data for an intermediate layer thickness of 0 nm shows the hardness measurement result of a sample that does not have an intermediate layer between the substrate and the coating layer (hereinafter referred to as a "non-inserted product").

[0057] As shown in Fig. 5, it was confirmed that all of samples No. 1 to No. 4 had a higher hardness than a non-inserted product when the intermediate layer was 40 nm thick. In particular, it was confirmed that sample No. 1, which is an embodiment of the present disclosure, had a significantly higher hardness when the intermediate layer was 40 nm thick. When the intermediate layer thickness was in the range of 20 nm or more and 80 nm or less, the hardness of the coating layer of sample No. 1 was 33.5 GPa or more.

[0058] On the other hand, it was confirmed that in all of samples No. 1 to No. 3, when the intermediate layer was 200 nm, the hardness of the coating layer was lower than when the intermediate layer was 40 nm. Also, it was confirmed that in samples No. 2 and No. 3, when the intermediate layer was 200 nm, the hardness of the coating layer was lower than that of the sample without the intermediate layer.

[0059] <Residual stress measurement> Fig. 6 is a graph showing the results of measuring the residual stress of the coating films of samples No. 1 to No. 4. The horizontal axis of the graph shown in Fig. 6 is the intermediate layer thickness (nm), and the vertical axis is the compressive residual stress (GPa).

[0060] In this disclosure, the measurement position of the residual stress is a position 1 mm or more inside (center side) from the cutting edge of the rake face or flank face. The residual stress was measured using an X-ray diffraction method. In this disclosure, the measurement was performed using the 2D method (multiaxial stress measurement method / full Debye ring fitting method) among the X-ray diffraction methods, but the measurement may be performed using a general X-ray diffraction device. In addition, the X-ray diffraction peak used to measure the residual stress was the peak of the TiAlN (422) plane that appears between 2θ values ​​of 125° and 135°. The residual stress was calculated using the Poisson's ratio of TiAlN = 0.21 and Young's modulus = 600,000 MPa. In addition, as the conditions for the X-ray diffraction measurement, CuKα rays were used as the X-ray source, and the residual stress was measured by irradiating it under the conditions of output = 45 kV and 120 mA. If the residual stress is positive, it is tensile stress, and if it is negative, it is compressive stress. The detailed measurement conditions are as follows.

[0061] <Measurement conditions> X-ray diffraction equipment: Bruker Japan D8 DISCOVER PlusIμS Source: CuKα Output: 45kV 120mA Collimator diameter: 0.5mmφ Measured diffraction line: TiAlN(422) surface 2θ≒129.990° Measurement method: 2D method (φ angle: 10°, 27.5°, 45°) Measurement time: 300sec / frame Measurement location: 1 mm or more inside (center side) from the cutting edge Swing: θ swing (swing width: θ = +2°) <Analysis method> The analysis was performed using the 2D method, with the following physical properties being used: TiAlN(422) surface Young's modulus: 600,000MPa Poisson's ratio: 0.21 2D method: Peak Evaluation: Pearson VII Stress model:Biaxial

[0062] In Figure 6, the data for an intermediate layer thickness of 0 nm indicates the residual stress of the coating layer formed directly on the substrate. Additionally, the data shown as squares in Figure 6 indicates the results of the compressive residual stress of the coating layer of sample No. 1. Additionally, the data shown as open circles in Figure 6 indicates the results of the compressive residual stress of the coating layer of sample No. 2. Additionally, the data shown as triangles in Figure 6 indicates the results of the compressive residual stress of the coating layer of sample No. 3. Additionally, the data shown as filled circles in Figure 6 indicates the results of the compressive residual stress of the coating layer of sample No. 4.

[0063] As shown in Figure 6, it was confirmed that the compressive residual stress of the coating layer decreases as the thickness of the intermediate layer increases, regardless of the composition of the intermediate layer. In particular, it was found that the compressive residual stress of the coating layer of sample No. 1, which has an intermediate layer containing Ti and Ar, is significantly reduced compared to the other samples No. 2 to No. 4. In the intermediate layer thickness range of 20 nm to 80 nm, the compressive residual stress of the coating layer of sample No. 1 was 1.45 GPa or less, specifically 1.4 GPa or less.

[0064] <Adhesion measurement> The adhesion of samples No. 1 to No. 4 was measured by a scratch test. The scratch test was performed using a diamond indenter with a tip shape of R (radius of curvature) of 200 μm, at a scratch speed of 10 mm / min and a load application speed of 100 N / min. In the scratch test, the load (peeling load) at which peeling occurred was evaluated as the adhesion. In the scratch test, the higher the critical load, the more difficult it is to peel, i.e., the higher the adhesion. FIG. 7 is a graph showing the results of the adhesion measurement. The horizontal axis of the graph shown in FIG. 7 is the intermediate layer thickness (nm), and the vertical axis is the peeling load (N). In FIG. 7, the data for an intermediate layer thickness of 0 nm shows the measurement results of the adhesion of the coating layer in a product without an intermediate layer inserted.

[0065] As shown in Fig. 7, it was confirmed that for all of Sample Nos. 1, 2, and 4, when the intermediate layer thickness was 40 nm, the adhesion was improved compared to the non-inserted product. In particular, for Sample No. 1 which is an example of the present disclosure, when the intermediate layer thickness was 40 nm, a remarkable improvement in adhesion was confirmed compared to other Sample Nos. 2 to 4. In the range of the intermediate layer thickness of 20 nm or more and 80 nm or less, the adhesion of Sample No. 1 was 110 N or more.

[0066] On the other hand, it was confirmed that for both Sample Nos. 1 and 2, when the intermediate layer was 200 nm, the adhesion decreased compared to the case where the intermediate layer was 40 nm. Also, for Sample No. 3, it was confirmed that there was no significant change in the adhesion of the coating layer regardless of the film thickness of the intermediate layer.

[0067] Fig. 8 is a table summarizing the results of the above-described hardness measurement, stress measurement, and adhesion measurement. In Fig. 8, the hardness, stress, and adhesion of each of Sample Nos. 1 to 3 are shown as percentages when the hardness, stress, and adhesion of the non-inserted product are set to 100% respectively.

[0068] As shown in Fig. 8, for Sample No. 1 which is an example of the present disclosure, when the intermediate layer thickness was 40 nm, the improvement in hardness and adhesion was remarkable compared to the non-inserted product and Sample Nos. 2 and 3. Also, for Sample No. 1, when the intermediate layer thickness was 40 nm, there was a remarkable effect of stress relaxation compared to the non-inserted product, and this effect was also remarkable compared to Sample Nos. 2 and 3.

[0069] From the above results, it can be seen that Sample No. 1 having an intermediate layer containing Ti and Ar is comprehensively excellent in terms of hardness improvement, stress relaxation, and adhesion improvement when the intermediate layer thickness is 40 nm.

[0070] <EDX surface analysis> Elemental analysis by EDX analysis was performed on Sample No. 1. The analysis conditions are as follows. (1) Sample pretreatment: Thinning by FIB method (μ-sampling method) (2) Elemental analysis (area analysis) (3) Scanning transmission electron microscope: JEOL JEM-ARM200F (4)Accelerating voltage: 200 kV (5) Irradiation current: about 7.5nA (6) Elemental analyzer: JED-2300T (7) Effective time: 60.0 seconds (8) Energy range: 0 keV to 40 keV

[0071] Fig. 9 is a diagram showing a Ti element mapping image in the intermediate layer of sample No. 1. Also, Fig. 10 is a diagram showing an Ar element mapping image in the intermediate layer of sample No. 1.

[0072] As is clear from the mapping images shown in Figures 9 and 10, the intermediate layer of sample No. 1 contains Ti and Ar. Also, as is clear from the Ar mapping image shown in Figure 10, the intermediate layer of sample No. 1 has a plurality of Ar-enriched regions distributed in an island shape. Also, as shown in Figure 10, it can be seen that the plurality of Ar-enriched regions are more distributed in the region of the intermediate layer closer to the substrate than to the center thereof, compared to the region of the intermediate layer closer to the coating layer than to the center in the thickness direction of the intermediate layer.

[0073] Fig. 11 is a table showing the element composition ratios in atomic % at measurement points P1 to P4 shown in Fig. 10. Note that measurement points P1 and P3 correspond to the Ar-enriched region, and measurement points P2 and P4 correspond to regions in the intermediate layer other than the Ar-enriched region.

[0074] As shown in Fig. 11, the Ar ratios at measurement points P1 and P3 in the Ar-enriched region were both 5 atomic %. In contrast, the Ar ratios at measurement points P2 and P4 outside the Ar-enriched region were 1 atomic %. From this result, it can be seen that the Ar-enriched region is a region in the intermediate layer that contains at least 3 atomic % Ar, specifically more than 1 atomic % Ar.

[0075] Furthermore, from the results shown in Fig. 11, it was confirmed that the intermediate layer of sample No. 1 contained, in addition to Ti and Ar, N, Al, Nb, Mo, and W. W was detected at measurement point P2 outside the Ar-enriched region, but was not detected at measurement points P1 and P3 in the Ar-enriched region.

[0076] Moreover, from the results shown in FIG. 11, it is understood that the intermediate layer of sample No. 1 contains at least 65 atomic % or more of Ti and 1 atomic % or more of Ar.

[0077] <Wear test> Wear tests were conducted on samples No. 1 to No. 4 (samples No. 1 to No. 3 had intermediate layer thicknesses of 10 nm, 20 nm, 40 nm, 80 nm, 120 nm, 160 nm, and 200 nm, and sample No. 4 had an intermediate layer thickness of 40 nm) and on samples without an intermediate layer. The wear tests were conducted under the following conditions using a cermet material for turning (model number: CNMG120408PQ). (1) Cutting method: Wet continuous cutting using Φ200 round material (2) Work material: SCМ435 (3) Feed: 0.20 mm / rev (4) Cutting depth ap: 1.0 mm (5) Evaluation method: The side flank wear (nose wear) after 60 minutes of machining was measured using a microscope.

[0078] Fig. 12 is a graph showing the results of the wear test. The horizontal axis of the graph shown in Fig. 12 is the intermediate layer thickness (nm), and the vertical axis is the ratio (wear resistance ratio) of the nose wear amount of the non-inserted product to the nose wear amount of the samples with each intermediate layer thickness. Specifically, the wear resistance ratio is the nose wear amount of the non-inserted product / the nose wear amount of each sample.

[0079] As shown in Fig. 12, in samples No. 1 to No. 3, when the intermediate layer thickness was in the range of 10 nm to 80 nm, the amount of wear was reduced compared to a product without an intermediate layer. From this result, it can be seen that samples No. 1 to No. 3 have higher wear resistance than a product without an intermediate layer when the intermediate layer thickness was in the range of 10 nm to 80 nm. It can also be seen that, among samples No. 1 to No. 3, sample No. 1 has particularly high wear resistance.

[0080] As described above, the insert according to the embodiment (for example, insert 1) has a base body (for example, base body 2) and a coating layer (for example, coating layer 3) that coats the surface of the base body. The base body is made of cermet. The coating layer is made of Ti 1-a-b-c-d Al a M b W c S d (C x N 1-x ) (wherein metal element M is one or more selected from Nb, Mo, Ta, Hf, and Y, and 0.40≦a≦0.55, 0.01≦b≦0.1, 0.01≦c≦0.1, 0.01≦d≦0.05, and 0≦x≦1.) In the insert according to one embodiment of the present disclosure, an intermediate layer containing Ti (intermediate layer 4, for example) is located between the substrate and the coating layer. The average thickness of the intermediate layer is 20 nm or more and 80 nm or less.

[0081] Therefore, the insert according to the embodiment can improve the wear resistance.

[0082] 1 is merely an example and does not limit the shape of the insert according to the present disclosure. The insert according to the present disclosure may have, for example, a rod-shaped main body having a rotation axis and extending from a first end to a second end, a cutting edge located at the first end of the main body, and a groove extending spirally from the cutting edge toward the second end of the main body.

[0083] Further advantages and modifications may readily occur to those skilled in the art. Thus, the disclosure in its broader aspects is not limited to the specific details and representative embodiments shown and described above. Thus, various modifications may be made without departing from the spirit or scope of the general inventive concept as defined by the appended claims and equivalents thereof. [Explanation of symbols]

[0084] 1 Insert 2 Base 3 Covering layer 4. Middle Tier 21 Through hole 41 Ar-enriched region 70 Holder 73 Pocket 75 Screw 100 cutting tools

Claims

1. A substrate and a coating layer that coats a surface of the substrate, The substrate is made of a cermet, The coating layer is made of Ti 1-a-b-c-d A a M b W c S d (C x N 1-x ) (wherein the metal element M is one or more selected from Nb, Mo, Ta, Hf, and Y, and 0.40≦a≦0.55, 0.01≦b≦0.1, 0.01≦c≦0.1, 0.01≦d≦0.05, and 0≦x≦1.) an intermediate layer containing Ti is located between the substrate and the coating layer; The average thickness of the intermediate layer is 20 nm or more and 80 nm or less, The intermediate layer contains at least 65 atomic % of Ti and at least 1 atomic % of Ar.

2. The insert according to claim 1 , wherein the coating layer has a hardness of 33.5 GPa or more and a compressive residual stress of 1.4 GPa or less.

3. The insert according to claim 1 , wherein the coating layer has an adhesive strength of 110 N or more in peel load in a scratch test.

4. a holder extending from a first end to a second end and having a pocket on the first end side; An insert according to any one of claims 1 to 3 located in the pocket; A cutting tool having

Citation Information

Patent Citations

  • Cutting tools made of surface-coated titanium carbonitride-based cermet with excellent toughness

    JP3099834B2

  • Coated cutting tool

    US20190161849A1

  • Cutting tool

    WO2009119682A1

  • Method for forming intermediate layer formed between substrate and DLC film, method for forming DLC film, and intermediate layer formed between substrate and DLC film

    WO2015068776A1

  • Coating and cutting tool

    WO2018216256A1